2013
DOI: 10.1103/physreve.87.062902
|View full text |Cite
|
Sign up to set email alerts
|

Ergodicity and quantum correlations in irrational triangular billiards

Abstract: Pseudochaotic properties are systematically investigated in a one-parameter family of irrational triangular billiards (all angles irrational with π). The absolute value of the position correlation function C(x)(t) decays like ~t(-α). Fast (α≈1) and slow (0<α<1) decays are observed, thus indicating that the irrational triangles do not share a unique ergodic dynamics, which, instead, may vary smoothly between the opposite limits of strong mixing (α=1) and regular behaviors (α=0). Upgrading previous data, spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Moreover, quantum systems with merely mixing (non-chaotic) classical counterparts can obey Wigner-Dyson distribution even without classical exponential instabilities (see, e.g., Ref. [19]). Such cases are considered outside of the BGS characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, quantum systems with merely mixing (non-chaotic) classical counterparts can obey Wigner-Dyson distribution even without classical exponential instabilities (see, e.g., Ref. [19]). Such cases are considered outside of the BGS characterization.…”
Section: Introductionmentioning
confidence: 99%
“…In the usual sense, building triangular billiards can be done easily by assigning rational or irrational values to the ratio between the inner angles of the triangle and π. Here, we follow the approach used by F. M. de Aguiar et al [8,9]. In order to construct the irrational triangular billiard, he has considered acute triangles with sides N, N + 1, and N + 2, where N is an integer.…”
Section: Modelmentioning
confidence: 99%
“…Positive K-S entropy or the chaotic property is assured only for the Kolmogorov and Bernoulli systems while pseudochaos is a partiular case of weak chaos with zero K-S entropy. In [8,9], it has been shown that the irrational triangular billiard can indeed exhibit the pseudochaotic property. Taking this into account, we would like to explore how the irrationality of a triangle or the pseudochaotic can affect the bipartite entanglement of the eigenmodes.…”
Section: Geometric Dependence Of Entanglement and The Irrationality Omentioning
confidence: 99%
See 2 more Smart Citations